Verb-second as a reconstruction phenomenon Evidence from grammar and processing - Freitag, Constantin (Studia grammatica, 2021)
This investigation of V2-movement addresses the question which role the lexical content of the moved element plays during sentence processing. It draws on original theoretical arguments, empirical data and results from psycholinguistic experiments. The main finding is that the lexical content of the V2-verb is interpreted only at the end of the clause, i.e. at the base position of the finite verb.